The Psychological Impact of COVID-19 Pandemic on Health Care Workers: A Systematic Review and Meta-Analysis - Sun, Ping; Wang, Manli; Song, Tingting; Wu, Yan; Luo, Jinglu; Chen, Lili; Yan, Lei (Frontiers in Psychology, 2021)
Objective: The COVID-19 epidemic has generated great stress throughout healthcare workers （HCWs）. The situation of HCWs should be fully and timely understood. The aim of this meta-analysis is to determine the psychological impact of COVID-19 pandemic on health care workers. Method: We searched the original literatures published from 1 Nov 2019 to 20 Sep 2020 in electronic databases of PUBMED, EMBASE and WEB OF SCIENCE. Forty-sevev studies were included in the meta-analysis with a combined total of 81277 participants. Results: The pooled prevalence of anxiety is 37% (95% CI 0.31-0.42, I2 = 99.9%) from 44 studies. Depression is estimated in 39 studies, and the pooled prevalence of depression is 36% (95% CI 0.31-0.41, I2 = 99.6%). There are 10 studies reported the prevalence of insomnia, and the overall prevalence of insomnia is 32% (95% CI 0.23-0.42, I2 =99.5%). The subgroup analysis showed a higher incidence of anxiety and depression among women and the frontline HCWs compared to men and non-frontline HCWs respectively. Conclusions: The COVID-19 pandemic has caused heavy psychological impact among healthcare professionals especially women and frontline workers. Timely psychological counselling and intervention ought to be implemented for HCWs in order to alleviate their anxiety and improve their general mental health.